Analysis of Plant Growth-Promoting Effects of Fluorescent Pseudomonas Strains Isolated from Mentha piperita Rhizosphere and Effects of Their Volatile Organic Compounds on Essential Oil Composition - Santoro, Maricel V.; Bogino, Pablo C.; Nocelli, Natalia; Cappellari, Lorena del Rosario; Giordano, Walter F.; Banchio, Erika (Frontiers in Microbiology, 2016)
Many species or strains of the genus Pseudomonas have been characterized as plant growth promoting rhizobacteria (PGPR). We used a combination of phenotypic and genotypic techniques to analyze the community of fluorescent Pseudomonas strains in the rhizosphere of commercially grown Mentha piperita (peppermint). Biochemical techniques, Amplified rDNA Restriction Analysis (ARDRA), and 16S rRNA gene sequence analysis revealed that the majority of the isolated native fluorescent strains were P. putida. Use of two Repetitive Sequence-based PCR (rep-PCR) techniques, BOX-PCR and ERIC-PCR, allowed us to evaluate diversity among the native strains and to more effectively distinguish among them. PGPR activity was tested for the native strains and reference strain P. fluorescens WCS417r. Micropropagated M. piperita plantlets were exposed to microbial volatile organic compounds (mVOCs) emitted by the bacterial strains, and plant biomass parameters and production of essential oils (EOs) were measured. mVOCs from 11 of the native strains caused an increase in shoot fresh weight. mVOCs from three native strains (SJ04, SJ25,SJ48) induced changes in M. pierita EO composition. The mVOCs caused a reduction of metabolites in the monoterpene pathway, for example menthofuran, and an increase in menthol production. Menthol production is the primary indicator of EO quality. The mVOCs produced by native strains SJ04, SJ25,SJ48 and strain WCS417r were analyzed. The obtained mVOC chromatographic profiles were unique for each of the three native strains analyzed, containing varying hydrocarbon, aromatic, and alogenic compounds. The differential effects of the strains were most likely due to the specific mixtures of mVOCs emitted by each strain, suggesting a synergistic effect occurs among the compounds present.